Covalent organic framework proton exchange membrane, preparation method thereof and high-temperature proton exchange membrane fuel cell

By using quaternary ammonium-type covalent organic frame nanosheets in high-temperature proton exchange membrane fuel cells to strong electrostatic interactions with phosphoric acid molecules, the problem of decreased proton conductivity under high temperature, low humidity or anhydrous conditions is solved, high phosphoric acid retention and high mechanical strength are achieved, and the performance of fuel cells is improved.

CN119786670APending Publication Date: 2025-04-08天津大学浙江研究院

Patent Information

Application Number
CN202411979773.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

The existing high-temperature proton exchange membrane fuel cells have decreased proton conductivity under high temperature, low humidity or anhydrous conditions, and phosphoric acid molecules are easily lost, resulting in a decrease in membrane stability and performance.

Method used

The quaternary ammonium amine monomer was synthesized under mild conditions and the quaternary ammonium covalent organic frame nanosheets were synthesized by phase transfer interface polymerization. The phosphate-loaded quaternary ammonium covalent organic frame proton exchange membrane was prepared in combination with vacuum-assisted self-assembly method to enhance the interaction force between the phosphoric acid molecules and the membrane.

Benefits of technology

High phosphoric acid retention, high water-anhydrous proton conductivity and high mechanical strength are achieved, and the energy conversion efficiency of high-temperature proton exchange membrane fuel cells is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119786670A_ABST
    Figure CN119786670A_ABST
Patent Text Reader

Abstract

The invention provides a covalent organic framework proton exchange membrane, a preparation method thereof and a high-temperature proton exchange membrane fuel cell. The preparation method comprises the following steps: dispersing 5-bromomethyl-dimethyl isophthalate and trimethylamine in alcohol to obtain a reaction solution, and performing water bath and rotary evaporation to obtain a first intermediate; dispersing the first intermediate in a hydrazine hydrate / ethanol mixed solution, reacting at 80-100 DEG C for 24-48 hours, and recrystallizing to obtain a second intermediate; dispersing the second intermediate and silver chloride in water, and carrying out inert gas reaction at 80-100 DEG C for 10 hours to obtain a quaternary ammonium type amine monomer; dissolving a quaternary ammonium type amine monomer and glacial acetic acid in water to obtain an amine monomer solution; the preparation method comprises the following steps: dissolving 1, 3, 5-benzenetricarboxaldehyde and 1, 4-dioxane in mesitylene to obtain an aldehyde monomer solution; adding the aldehyde monomer solution above the amine monomer solution to obtain an interfacial polymerization reaction system, reacting at 16-40 DEG C for 7 days, and filtering to obtain a nanosheet dispersion liquid; dropwise adding the dispersion liquid into a suction filtration container, performing vacuum suction filtration to form a membrane, and then adding a phosphoric acid solution to enable phosphoric acid molecules to enter the membrane to obtain the covalent organic framework proton exchange membrane.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to the technical field of proton exchange membrane material preparation, and in particular to a covalent organic framework proton exchange membrane and a preparation method thereof, and a high-temperature proton exchange membrane fuel cell. Background Art

[0002] High-temperature proton exchange membrane fuel cells have attracted much attention due to their advantages such as high CO tolerance, high kinetic reaction rate, and simple water and heat management. Commercial Nafion membranes and other membranes lose water molecules rapidly under high temperature, low humidity or anhydrous conditions, significantly reduce the proton dissociation ability and connectivity of proton transfer channels, and the proton conductivity decreases by 2-3 orders of magnitude. Therefore, the current commercial Nafion membranes are not suitable for high temperature, low humidity or anhydrous conditions.

[0003] In order to improve the proton conductivity under high temperature, low humidity or anhydrous conditions, strategies such as improving the membrane's water retention capacity and loading low-volatile proton carriers (ionic liquids, phosphoric acid) are usually used to improve the membrane's proton conductivity. Phosphoric acid molecules have a low vacuum dissociation energy, and complexing with alkaline polymers is an effective way to prepare high-temperature proton exchange membranes. For example, phosphoric acid-doped polybenzimidazole membrane (PBI) is currently the main type of proton exchange membrane used in high-temperature fuel cells due to its excellent thermal and chemical stability, good mechanical properties and proton conductivity. However, PBI has poor processability, and increasing the phosphoric acid loading will lead to a decrease in membrane strength, which restricts further improvement in proton conductivity. In order to improve the proton conductivity and stability of phosphoric acid-loaded proton exchange membranes under high temperature conditions, it is necessary to have a connected proton transfer channel and a strong interaction with phosphoric acid molecules. The proton transfer channel in the high-temperature proton exchange membrane is composed of the phosphoric acid loading area, but its connectivity is poor, which restricts the improvement of the membrane's proton conductivity. On the other hand, the channel wall has a weak interaction with the phosphoric acid molecules, and the phosphoric acid molecules are easily lost, causing the proton conductivity to decay.

[0004] Covalent organic porous framework materials (COF) are composed of light elements (C, H, O, N, B, Si, S, etc.) connected by reversible dynamic covalent chemical bonds to form a two-dimensional or three-dimensional skeleton structure. At present, COFs are mainly used for high-temperature proton conductors in the form of powder tablets or fillers, and the defects between powder particles become the main resistance to proton conduction. Although COF membranes can reduce the generation of interface defects to a certain extent and make the proton transfer channel more continuous. However, the COF membranes currently obtained in the form of powder tablets or fillers have weak interaction forces with phosphoric acid molecules, which significantly reduces the proton conductivity of the membrane in practical applications, thereby resulting in a decrease in battery performance. Summary of the invention

[0005] The present disclosure provides a covalent organic framework proton exchange membrane and a preparation method thereof, and a high-temperature proton exchange membrane fuel cell, so as to at least solve one of the technical problems existing in the prior art.

[0006] According to a first aspect of the present disclosure, a method for preparing a covalent organic framework proton exchange membrane is provided, comprising:

[0007] (1) Synthesis of quaternary ammonium amine monomers:

[0008] Dispersing 5-bromomethyl-dimethyl isophthalate, trimethylamine or triethylamine in alcohol to obtain a reaction solution, placing the reaction solution in a water bath at 25-40° C., stirring, rotary evaporating, and drying to obtain a first intermediate;

[0009] The first intermediate is dispersed in a hydrazine hydrate solution and ethanol is added, and the reaction is carried out at 80-100° C. for 24-48 hours. After the reaction is completed, the second intermediate is obtained by recrystallization, alcohol washing, and drying.

[0010] Dispersing the second intermediate and silver chloride in water, reacting at 80-100° C. in an inert gas atmosphere for at least 10 hours, filtering and rotary evaporating after the reaction to obtain the quaternary ammonium amine monomer;

[0011] (2) Synthesis of quaternary ammonium covalent organic framework nanosheet dispersion:

[0012] The quaternary ammonium amine monomer and glacial acetic acid are dissolved in water and ultrasonically dispersed to obtain an amine monomer solution; trimesaldehyde and 1,4-dioxane are dissolved in mesitylene and ultrasonically dispersed to obtain an aldehyde monomer solution;

[0013] Slowly adding the aldehyde monomer solution onto the amine monomer solution to obtain an interfacial polymerization reaction system, placing the interfacial polymerization reaction system at 16-40° C. and reacting for at least 7 days to obtain an aqueous solution; filtering and dialyzing the aqueous solution to obtain a quaternary ammonium covalent organic framework nanosheet dispersion;

[0014] (3) Preparation of covalent organic framework proton exchange membrane:

[0015] The quaternary ammonium covalent organic framework nanosheet dispersion is added dropwise to a filtration container, vacuum-assisted filtration is performed to form a membrane, and then a phosphoric acid solution is added to allow the phosphoric acid molecules to enter the quaternary ammonium covalent organic framework membrane through negative pressure to obtain a quaternary ammonium covalent organic framework proton exchange membrane loaded with phosphoric acid.

[0016] In one embodiment, in step (1), the mass volume ratio of 5-bromomethyl-dimethyl isophthalate to trimethylamine is 4-8 g: 6-12 ml;

[0017] Alternatively, the mass volume ratio of the 5-bromomethyl-dimethyl isophthalate to triethylamine is 4-8 g:6-12 ml.

[0018] In one embodiment, in step (1), the mass volume ratio of the first intermediate to the hydrazine hydrate solution is 4-6 g:9-11 ml; wherein the concentration of the hydrazine hydrate solution is 20% to 40%.

[0019] In one possible implementation manner, in the step (1), the mass ratio of the second intermediate to silver chloride is 1.56:0.64-1.92.

[0020] In one embodiment, in the step (2), the molar ratio of the quaternary ammonium amine monomer to trimesaldehyde is 3:2 to 1:2.

[0021] In one embodiment, in step (2), the total volume of the glacial acetic acid and water is the same as the total volume of 1,4-dioxane and mesitylene.

[0022] In one possible implementation manner, in the step (3), the vacuum-assisted filtration membrane formation adopts a vacuum circulating water pump vacuum-assisted method to prepare the membrane.

[0023] In one embodiment, in step (3), the concentration of the added phosphoric acid solution is 1-6M.

[0024] According to a second aspect of the present disclosure, the present invention provides a covalent organic framework proton exchange membrane, which is prepared by the preparation method described in any one of the above-mentioned embodiments.

[0025] According to a third aspect of the present disclosure, the present invention provides a high-temperature proton exchange membrane fuel cell, comprising the covalent organic framework proton exchange membrane prepared by the preparation method, or the covalent organic framework proton exchange membrane.

[0026] Compared with the prior art, the advantages of the present invention are: (1) the method of the present invention can synthesize quaternary ammonium amine monomers (such as Mbh-N + (CH3)3Cl - powder), and synthesized quaternary ammonium covalent organic framework nanosheets (e.g., TpMbh-N + (CH3)3Cl - Nanosheets), phosphate-loaded quaternary ammonium covalent organic framework proton exchange membranes (e.g. H3PO4@TpMbh-N + (CH3)3Cl - The preparation method is simple and easy to operate. (2) In the present application, the quaternary ammonium covalent organic framework nanosheet (such as TpMbh-N + (CH3)3Cl -) and the strong electrostatic interaction between phosphate molecules, achieving high phosphate retention, high anhydrous proton conductivity and high mechanical strength. (3) In addition, the H3PO4@TpMbh-N + (CH3)3Cl - Proton exchange membrane is used in high-temperature proton exchange membrane fuel cells and has high energy conversion efficiency.

[0027] It should be understood that the content described in this section is not intended to identify the key or important features of the embodiments of the present disclosure, nor is it intended to limit the scope of the present disclosure. Other features of the present disclosure will become easily understood through the following description. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] The above and other objects, features and advantages of the exemplary embodiments of the present disclosure will become readily understood by reading the detailed description below with reference to the accompanying drawings. In the accompanying drawings, several embodiments of the present disclosure are shown in an exemplary and non-limiting manner, in which:

[0029] In the drawings, the same or corresponding reference numerals represent the same or corresponding parts.

[0030] Figure 1 A scanning electron microscope image of the proton exchange membrane of Example 1 of the present disclosure is shown;

[0031] Figure 2 A graph showing the proton conductivity of the proton exchange membrane of Example 1 of the present disclosure as a function of temperature is shown;

[0032] Figure 3 shows a stress-strain curve diagram of the proton exchange membrane of Example 1 of the present disclosure;

[0033] Figure 4 A high temperature fuel cell performance diagram showing the proton exchange membrane prepared according to Example 1 of the present disclosure;

[0034] Figure 5 A graph showing the proton conductivity of the proton exchange membrane of Example 2 of the present disclosure as a function of temperature is shown;

[0035] Figure 6 shows a stress-strain curve diagram of the proton exchange membrane of Example 2 of the present disclosure;

[0036] Figure 7 A graph showing the proton conductivity of the proton exchange membrane of Comparative Example 1 of the present disclosure as a function of temperature is shown;

[0037] Figure 8 The stress-strain curve of the proton exchange membrane of Comparative Example 1 of the present disclosure is shown. DETAILED DESCRIPTION

[0038] In order to make the purpose, features, and advantages of the present disclosure more obvious and easy to understand, the technical solutions in the embodiments of the present disclosure will be clearly and completely described below in conjunction with the drawings in the embodiments of the present disclosure. Obviously, the described embodiments are only part of the embodiments of the present disclosure, not all of the embodiments. Based on the embodiments in the present disclosure, all other embodiments obtained by those skilled in the art without creative work are within the scope of protection of the present disclosure.

[0039] Based on the advantages of COF regular pore structure and quaternary ammonium groups in inhibiting the loss of phosphate molecules, the present invention provides a method for preparing a phosphate-loaded quaternary ammonium covalent organic framework proton exchange membrane (referred to as "covalent organic framework membrane").

[0040] Specifically, according to one embodiment of the present disclosure, the present invention provides a method for preparing a covalent organic framework proton exchange membrane, the preparation method comprising:

[0041] Step (1) Synthesis of quaternary ammonium amine monomer:

[0042] Dispersing 5-bromomethyl-dimethyl isophthalate, trimethylamine or triethylamine in alcohol to obtain a reaction solution, placing the reaction solution in a water bath at 25-40° C., stirring, rotary evaporating, and drying to obtain a first intermediate;

[0043] The first intermediate is dispersed in a hydrazine hydrate solution and ethanol is added, and the reaction is carried out at 80-100° C. for 24-48 hours. After the reaction is completed, the second intermediate is recrystallized, washed with alcohol, and dried to obtain a second intermediate.

[0044] The second intermediate and silver chloride are dispersed in water, and reacted at 80-100° C. in an inert gas atmosphere for at least 10 hours. After the reaction is completed, the reaction is filtered and rotary evaporated to obtain the quaternary ammonium amine monomer.

[0045] For example, the mass volume ratio of the 5-bromomethyl-dimethyl isophthalate to trimethylamine is 4-8 g:6-12 ml; preferably, the mass volume ratio of the 5-bromomethyl-dimethyl isophthalate to trimethylamine is 5 g:10 ml.

[0046] Or, the mass volume ratio of the 5-bromomethyl-dimethyl isophthalate to triethylamine is 4-8 g:6-12 ml; preferably, the mass volume ratio of the 5-bromomethyl-dimethyl isophthalate to triethylamine is 5 g:10 ml.

[0047] For example, 5-bromomethyl-dimethyl isophthalate, trimethylamine or triethylamine are dispersed in alcohol to obtain a reaction solution, and the reaction solution is placed in a water bath at 25-40°C, stirred, rotary evaporated, and dried to obtain a first intermediate, with a stirring time of at least 12 hours, a rotary evaporation temperature of 60-80°C (preferably 70°C), and a drying temperature of 80°C.

[0048] For example, the mass volume ratio of the first intermediate to the hydrazine hydrate solution is 4-6 g:9-11 ml, wherein the concentration of the hydrazine hydrate solution is 20% to 40%. Preferably, the mass volume ratio of the first intermediate to the hydrazine hydrate solution is 5 g:10 ml.

[0049] For example, the first intermediate is dispersed in a hydrazine hydrate solution and ethanol is added, and the reaction is carried out at 80-100°C for 24-48 hours. After the reaction, the second intermediate is obtained by recrystallization, alcohol washing, and drying. When the reaction temperature is 80-100°C, condensation reflux and reaction for 24-48 hours can be further used. The recrystallization is carried out by using an acetone aqueous solution and heating to boiling. The alcohol washing is carried out by ethanol washing.

[0050] For example, the mass ratio of the second intermediate to silver chloride is 1.56-0.64:1.92; preferably, the mass ratio of the second intermediate to silver chloride is 1.56:1.28.

[0051] For example, in the step (1), the second intermediate and silver chloride are dispersed in water, reacted at 80-100° C. in an inert gas atmosphere for at least 10 hours, filtered and rotary evaporated to obtain the quaternary ammonium amine monomer, and the rotary evaporation temperature is 60-80° C. Preferably, the reaction temperature is 90° C. and the reaction is carried out in a N2 atmosphere for 10 hours.

[0052] Step (2) Synthesis of quaternary ammonium covalent organic framework nanosheet dispersion:

[0053] The quaternary ammonium amine monomer and glacial acetic acid are dissolved in water and ultrasonically dispersed to obtain an amine monomer solution; trimesaldehyde and 1,4-dioxane are dissolved in mesitylene and ultrasonically dispersed to obtain an aldehyde monomer solution;

[0054] The aldehyde monomer solution is slowly added onto the amine monomer solution to obtain an interfacial polymerization reaction system, and the interfacial polymerization reaction system is placed at 16-40° C. and reacted for at least 7 days to obtain an aqueous solution; the aqueous solution is filtered and dialyzed to obtain a quaternary ammonium covalent organic framework nanosheet dispersion.

[0055] For example, in step (2), the molar ratio of the quaternary ammonium amine monomer to trimesaldehyde is 3:2 to 1:2. Preferably, in step (2), the molar ratio of the quaternary ammonium amine monomer to trimesaldehyde is 3:2.

[0056] For example, in step (2), the total volume of the glacial acetic acid and water is the same as the total volume of 1,4-dioxane and mesitylene.

[0057] For example, in step (2), dialysis is performed using a dialysis bag with a molecular weight of 30,000 Da and the dialysis is performed for 4 days.

[0058] Step (3) Preparation of covalent organic framework proton exchange membrane:

[0059] The quaternary ammonium covalent organic framework nanosheet dispersion is added dropwise to a filtration container, vacuum-assisted filtration is performed to form a membrane (i.e., a quaternary ammonium covalent organic framework membrane is obtained), and then a phosphoric acid solution is added to allow the phosphoric acid molecules to enter the quaternary ammonium covalent organic framework membrane through negative pressure to obtain a quaternary ammonium covalent organic framework proton exchange membrane loaded with phosphoric acid (i.e., a phosphoric acid-loaded quaternary ammonium covalent organic framework proton exchange membrane).

[0060] For example, in the step (3), the vacuum film forming is carried out by using a vacuum circulating water pump vacuum assisted method to prepare the film.

[0061] For example, in step (3), the concentration of the added phosphoric acid solution is 1 to 6M.

[0062] The membrane preparation process of the present application mainly includes synthesizing quaternary ammonium amine monomers (such as Mbh-N + (CH3)3Cl - powder), and synthesized quaternary ammonium covalent organic framework nanosheet dispersions (e.g., TpMbh-N + (CH3)3Cl - Nanosheets), phosphate-loaded quaternary ammonium covalent organic framework proton exchange membranes (e.g. H3PO4@TpMbh-N + (CH3)3Cl - Proton exchange membrane), the preparation method is simple to operate and easy to implement.

[0063] The present application scheme can adjust the strength of the local electrostatic force by precisely adjusting the length of the alkyl chain of the quaternary ammonium group, while the hydrophobicity and steric retardation of the side chain can also mediate the distribution of H3PO4 molecules in the membrane.

[0064] In the preparation method of the present invention, a quaternary ammonium covalent organic framework nanosheet dispersion (such as TpMbh-N + (CH3)3Cl - ) and the strong electrostatic interaction between phosphate molecules, achieving high phosphate retention rate, high anhydrous proton conductivity and high mechanical strength. + (CH3)3Cl - Proton exchange membrane is used in high-temperature proton exchange membrane fuel cells and has high energy conversion efficiency.

[0065] The proton exchange membrane prepared by the present invention (e.g. H3PO4@TpMbh-N + (CH3)3Cl - ) Compared with traditional polyelectrolytes and COF powders, the proton exchange membrane (H3PO4@TpMbh-N +(CH3)3Cl - The membrane provides well-defined one-dimensional channels, constructs a highly interconnected hydrogen bond network derived from H3PO4 molecules, and the introduction of strong electrostatic and capillary interactions greatly stabilizes the H3PO4 molecules in the nanochannels and improves the retention capacity of H3PO4. These synergistic effects make H3PO4@TpMbh-N + (CH3)3Cl - The membrane is able to achieve excellent H3PO4 retention and high proton conductivity under high-temperature anhydrous conditions, effectively solving the key challenges in high-temperature proton exchange membrane fuel cells.

[0066] According to one embodiment of the present disclosure, the present invention also provides a covalent organic framework proton exchange membrane, which is prepared by the preparation method described above.

[0067] According to one embodiment of the present disclosure, the present invention also provides a high-temperature proton exchange membrane fuel cell, comprising the covalent organic framework proton exchange membrane prepared by the above preparation method, or the covalent organic framework proton exchange membrane.

[0068] The present application is further described in detail below with reference to specific embodiments:

[0069] Example 1

[0070] A method for preparing a phosphate-loaded quaternary ammonium covalent organic framework proton exchange membrane (referred to as "covalent organic framework membrane") comprises the following steps:

[0071] Step 1, synthesis of quaternary ammonium amine monomer:

[0072] Weigh 5 g (17.4 mmol) of 5-bromomethyl-dimethyl isophthalate and 10 ml of trimethylamine and disperse them in 50 ml of ethanol to obtain a reaction solution, place it in a 40° C. water bath, stir it for 12 hours, then perform rotary evaporation (70° C.) and dry it (80° C.) to obtain a first intermediate; disperse 5 g of the first intermediate obtained above in 10 ml of hydrazine hydrate solution (concentration 40%) and add 50 ml of ethanol, and react at 90° C. for 36 hours; after the reaction is completed, recrystallize, wash with ethanol, and dry to obtain a second intermediate, which is recorded as Mbh-N + (CH3)3Br - 1.56 g (4.5 mmol) of Mbh-N + (CH3)3Br - and 1.28 g (9.2 mmol) of silver chloride were dispersed in 15 ml of water and reacted at 90 ° C in a nitrogen atmosphere for 10 h. After the reaction, 3,5-diformylhydrazide-benzyltrimethylammonium chloride (i.e., quaternary ammonium amine monomer) was obtained by filtration and rotary evaporation, which was recorded as Mbh-N + (CH3)3Cl- .

[0073] Step 2, Synthesis of quaternary ammonium covalent organic framework nanosheet dispersion:

[0074] 226 mg (0.75 mmol) of Mbh-N obtained in step 1 was added + (CH3)3Cl - and 5 ml of glacial acetic acid were dissolved in 95 ml of water and ultrasonically dispersed for 30 min to obtain an amine monomer solution; 105 mg (0.5 mmol) of trimesaldehyde and 5 ml of 1,4-dioxane were dissolved in 95 ml of mesitylene and ultrasonically dispersed for 30 min to obtain an aldehyde monomer solution; the aldehyde monomer solution was slowly added to the top of the amine monomer solution to obtain an interfacial polymerization reaction system, and the interfacial polymerization reaction system was placed in an oven at 25°C for 7 days to obtain an aqueous solution; the obtained aqueous solution was filtered and dialyzed to obtain a quaternary ammonium covalent organic framework nanosheet dispersion, recorded as TpMbh-N + (CH3)3Cl - .

[0075] Step 3: Preparation of quaternary ammonium covalent organic framework proton exchange membrane supported by phosphate: 10 mL of TpMbh-N + (CH3)3Cl - The nanosheet dispersion was added dropwise to a 1.76 cm 2 In the filter cup, the membrane was prepared by vacuum circulation water pump vacuum assisted method. + (CH3)3Cl - When the membrane preparation is completed, 10 mL of phosphoric acid solution is added to the filter cup. The concentration of the phosphoric acid solution is 6 mol / L. After the phosphoric acid solution is drained, a phosphoric acid-loaded quaternary ammonium covalent organic framework proton exchange membrane is obtained, which is recorded as H3PO4@TpMbh-N + (CH3)3Cl - .

[0076] After testing, the H3PO4@TpMbh-N prepared in Example 1 + (CH3)3Cl - The proton conductivity of the membrane is 379.7 mS.cm -1 (200℃), mechanical strength is 42.2MPa.

[0077] Example 2

[0078] The preparation process of the phosphate-loaded quaternary ammonium covalent organic framework proton exchange membrane of Example 2 is basically the same as that of Example 1, except that in step 1, the trimethylamine solution is replaced with triethylamine, and the finally obtained proton exchange membrane is recorded as H3PO4@TpMbh-N + (C2H5)3Cl - .

[0079] After testing, the H3PO4@TpMbh-N prepared in Example 2 + (C2H5)3Cl - The proton conductivity of the membrane is 213.7 mS.cm -1 (200℃), mechanical strength is 46.9MPa.

[0080] Comparative Example 1

[0081] The preparation process of the phosphate-loaded quaternary ammonium covalent organic framework proton exchange membrane of Comparative Example 1 is basically the same as that of Example 1, except that in step 1, the trimethylamine solution is replaced with tri-n-propylamine, and the membrane finally obtained is recorded as H3PO4@TpMbh-N + (C3H7)3Cl - .

[0082] After testing, the H3PO4@TpMbh-N prepared in Comparative Example 1 + (C3H7)3Cl - The proton conductivity of the membrane is 167.1mS.cm -1 (200℃), mechanical strength is 43.9MPa.

[0083] The proton conductivity and mechanical strength of the proton exchange membranes prepared in the above examples and comparative examples are listed in Table 1, respectively.

[0084] Table 1 Test data of the embodiments of the present invention and the comparative examples

[0085] <![CDATA[Proton conductivity / mS.cm -1 > Mechanical strength / MPa Example 1 379.7 42.2 Example 2 213.7 46.9 Comparative Example 1 167.1 43.9

[0086] According to the preparation conditions and Table 1 of all the above embodiments and Comparative Example 1, it can be concluded that: as the length of the side chain increases, the electron donation effect of the longer alkyl chain will enhance the electron cloud density around the quaternary ammonium group, thereby generating a stronger electrostatic interaction. However, the longer side chain (Comparative Example 1) will enhance the hydrophobic interaction and generate steric hindrance, thereby destroying the uniform electrostatic interaction. Thus, the uniform distribution of H3PO4 in the quaternary ammonium covalent organic framework is destroyed. If the uniform distribution of H3PO4 in the nanochannel is destroyed, the overall H3PO4 content is reduced, and the efficiency of the effective proton transport pathway is ultimately reduced.

[0087] Characterization and Testing:

[0088] 1) Electron microscope photo of the proton exchange membrane prepared in Example 1 Figure 1 shown.

[0089] from Figure 1 It can be seen that the cross-sectional structure of the proton exchange membrane is relatively dense and has no obvious interface defects.

[0090] II): The proton conductivity and temperature variation diagram of the proton exchange membrane prepared in Example 1, the results are as follows Figure 2 shown.

[0091] from Figure 2 It can be seen that from 40°C to 200°C, as the temperature increases, the proton conductivity of the proton exchange membrane of Example 1 increases from 25.3 mS.cm -1 Increased to 379.7mS.cm -1 , the proton conductivity increased significantly.

[0092] III): The stress-strain diagram of the proton exchange membrane prepared in Example 1 is as follows Figure 3 As shown. Figure 3 It can be concluded that the stress of the proton exchange membrane prepared in Example 1 is 42.2 MPa. This is because the strong π-π interaction between COF nanosheets gives the proton exchange membrane high mechanical strength.

[0093] IV): The proton exchange membrane prepared in Example 1 was further used to prepare a high-temperature proton exchange membrane fuel cell and tested (a membrane electrode (MEA) was prepared by a binder bonding method). The specific operation was as follows: First, 40% Pt / C catalyst, Nafion isopropanol solution and deionized water were mixed and ultrasonicated to prepare a dispersion. Subsequently, the dispersion was sprayed on the surface of a hydrophobic carbon paper (0.2 mg.cm -2 ), then the two catalyst layers and the proton exchange membrane are stacked and compacted to form an MEA. Finally, the MEA is sealed between the two electrodes of the single cell. The study used the NBT-PEM-25W battery test system at 100 mL.min -1 Hydrogen flow rate and 100mL.min -1 The test was conducted under the condition of oxygen flow rate). The results are as follows Figure 4 shown.

[0094] from Figure 4 It can be concluded that high proton conductivity and strong mechanical strength give proton exchange membranes excellent high-temperature fuel cell performance.

[0095] When used in high temperature fuel cells, the maximum power density of Example 1 is 330 mW.cm -2 (160℃).

[0096] V): The proton conductivity and temperature variation results of the proton exchange membrane prepared in Example 2 are as follows: Figure 5 shown.

[0097] from Figure 5It can be concluded that when the temperature increases from 40°C to 200°C, the proton conductivity of the proton exchange membrane prepared in Example 2 increases from 16.2 mS.cm -1 Gradually increased to 213.7mS.cm -1 .

[0098] VI): The stress-strain curve of the proton exchange membrane prepared in Example 2 is as follows Figure 6 As shown. Figure 6 It can be concluded that the stress of the proton exchange membrane prepared in Example 2 is 46.9 MPa. This is because the strong π-π interaction between the COF nanosheets gives the proton exchange membrane high mechanical strength.

[0099] VII): The proton conductivity of the proton exchange membrane prepared in Comparative Example 1 changes with temperature. The results are as follows Figure 7 shown.

[0100] from Figure 7 It can be concluded that the proton conductivity of the proton exchange membrane prepared in Comparative Example 1 is from 11.1 mS.cm -1 Gradually increased to 167.1mS.cm -1 Compared with the proton conductivity of the proton exchange membranes of Examples 1-2, the proton conductivity of the proton exchange membrane obtained in Comparative Example 1 is smaller than that of Examples 1-2, and especially much smaller than that of the proton exchange membrane of Example 1. This is because the proton exchange membrane of Example 1 has larger pores and specific surface area, and the quaternary ammonium groups in the pores also have stronger electrostatic force to bind H3PO4 molecules, thereby increasing the H3PO4 loading and reducing the proton transfer resistance.

[0101] Eight): The stress-strain curve results of the proton exchange membrane prepared in Comparative Example 1 are as follows Figure 8 shown.

[0102] from Figure 8 It can be concluded that the stress of the proton exchange membrane prepared in Comparative Example 1 is 43.9 MPa, and the strong π-π interaction between COF nanosheets gives the proton exchange membrane high mechanical strength.

[0103] It should be understood that the various forms of processes shown above can be used to reorder, add or delete steps. For example, the steps recorded in this disclosure can be executed in parallel, sequentially or in different orders, as long as the desired results of the technical solutions disclosed in this disclosure can be achieved, and this document does not limit this.

[0104] In addition, the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of technical features indicated. Thus, a feature defined as "first" or "second" may explicitly or implicitly include at least one of the features. In the description of the present disclosure, the meaning of "plurality" is two or more, unless otherwise clearly and specifically defined.

[0105] The above is only a specific embodiment of the present disclosure, but the protection scope of the present disclosure is not limited thereto. Any person skilled in the art who is familiar with the technical field can easily think of changes or substitutions within the technical scope disclosed in the present disclosure, which should be included in the protection scope of the present disclosure. Therefore, the protection scope of the present disclosure should be based on the protection scope of the claims.

Claims

1. A method for preparing a covalent organic framework proton exchange membrane, characterized in that: include: (1) Synthesis of quaternary ammonium amine monomers: Dispersing 5-bromomethyl-dimethyl isophthalate, trimethylamine or triethylamine in alcohol to obtain a reaction solution, placing the reaction solution in a water bath at 25-40° C., stirring, rotary evaporating, and drying to obtain a first intermediate; The first intermediate is dispersed in a hydrazine hydrate solution and ethanol is added, and the reaction is carried out at 80-100° C. for 24-48 hours. After the reaction is completed, the second intermediate is obtained by recrystallization, alcohol washing, and drying. Dispersing the second intermediate and silver chloride in water, reacting at 80-100° C. in an inert gas atmosphere for at least 10 hours, filtering and rotary evaporating after the reaction to obtain the quaternary ammonium amine monomer; (2) Synthesis of quaternary ammonium covalent organic framework nanosheet dispersion: The quaternary ammonium amine monomer and glacial acetic acid are dissolved in water and ultrasonically dispersed to obtain an amine monomer solution; trimesaldehyde and 1,4-dioxane are dissolved in mesitylene and ultrasonically dispersed to obtain an aldehyde monomer solution; Slowly adding the aldehyde monomer solution onto the amine monomer solution to obtain an interfacial polymerization reaction system, placing the interfacial polymerization reaction system at 16-40° C. and reacting for at least 7 days to obtain an aqueous solution; filtering and dialyzing the aqueous solution to obtain a quaternary ammonium covalent organic framework nanosheet dispersion; (3) Preparation of covalent organic framework proton exchange membrane: The quaternary ammonium covalent organic framework nanosheet dispersion is added dropwise to a filtration container, vacuum-assisted filtration is performed to form a membrane, and then a phosphoric acid solution is added to allow the phosphoric acid molecules to enter the quaternary ammonium covalent organic framework membrane through negative pressure to obtain the covalent organic framework proton exchange membrane.

2. The preparation method according to claim 1, characterized in that: In the step (1), the mass volume ratio of the 5-bromomethyl-dimethyl isophthalate to trimethylamine is 4-8 g: 6-12 ml; Alternatively, the mass volume ratio of the 5-bromomethyl-dimethyl isophthalate to triethylamine is 4-8 g:6-12 ml.

3. The preparation method according to claim 1, characterized in that: In the step (1), the mass volume ratio of the first intermediate to the hydrazine hydrate solution is 4-6 g:9-11 ml; wherein the concentration of the hydrazine hydrate solution is 20% to 40%.

4. The preparation method according to claim 1, characterized in that: In the step (1), the mass ratio of the second intermediate to silver chloride is 1.56:0.64-1.

92.

5. The preparation method according to claim 1, characterized in that: In the step (2), the molar ratio of the quaternary ammonium amine monomer to trimesaldehyde is 3:2 to 1:

2.

6. The preparation method according to claim 1, characterized in that: In the step (2), the total volume of the glacial acetic acid and water is the same as the total volume of 1,4-dioxane and mesitylene.

7. The preparation method according to claim 1, characterized in that: In the step (3), the vacuum-assisted filtration membrane formation adopts a vacuum circulating water pump vacuum-assisted method to prepare the membrane.

8. The preparation method according to claim 1, characterized in that: In the step (3), the concentration of the added phosphoric acid solution is 1 to 6M.

9. A covalent organic framework proton exchange membrane, characterized in that: It is prepared by the preparation method described in any one of claims 1 to 8.

10. A high temperature proton exchange membrane fuel cell, characterized in that: The invention comprises a covalent organic framework proton exchange membrane prepared by the preparation method according to any one of claims 1 to 8, or a covalent organic framework proton exchange membrane according to claim 9.

Citation Information

Patent Citations

  • Covalent organic framework-based composite anion exchange membrane with high quaternary ammonium content and preparation method of covalent organic framework-based composite anion exchange membrane

    CN118440486A

  • Phosphoric Acid Loaded Covalent Organic Framework And A Process For The Preparation Thereof

    US20150299147A1

  • Method of making a copolymer of tetrafluoroethylene having sulfonyl pendant groups

    US20180273663A1

  • Proton exchange membrane with enhanced chemical stability and method of preparing thereof

    US20200343569A1

Cited By

  • Preparation method and application of sulfonated covalent organic framework modified perfluorinated sulfonic acid resin composite proton exchange membrane

    CN121930520A